2005
DOI: 10.1507/endocrj.52.407
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Sex Hormone-Binding Globulin and Pregnancy Outcome in Women Undergoing Controlled Ovarian Hyperstimulation for Assisted Reproduction

Abstract: Abstract. The purpose of this study was to determine whether the changes of sex hormone-binding globulin (SHBG) affect the pregnancy outcome in women undergoing controlled ovarian hyperstimulation (COH) for assisted reproduction. Forty-five infertile women who were undergoing pituitary desensitization and COH for in vitro fertilization (IVF) with or without intracytoplasmic sperm injection (ICSI) and 19 women with normal menstrual cycles participated in the study. Fasting blood samples of the follicular and lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
5
2
2
Order By: Relevance
“…Finally, in our study no association was found between the serum and follicular fluid SHBG levels and pregnancy outcome, whereas previous studies have shown conflicting results [14,15]. The concentrations of SHBG in stimulated cycles in both serum and follicular fluid are not statistically different between women who conceived and those who did not.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Finally, in our study no association was found between the serum and follicular fluid SHBG levels and pregnancy outcome, whereas previous studies have shown conflicting results [14,15]. The concentrations of SHBG in stimulated cycles in both serum and follicular fluid are not statistically different between women who conceived and those who did not.…”
Section: Discussioncontrasting
confidence: 86%
“…An increase of SHBG levels in serum and follicular fluid is observed during ovarian stimulation for IVF, presumably to regulate the bioactivity of sex steroids [12,13]. Conflicting results exist concerning its ability to affect fertilisation rates and pregnancy outcomes [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Oral, but not trans-dermal, administration of estradiol stimulated the synthesis of SHBG (40). Serum SHBG concentrations did not vary during the follicular and luteal phases of the menstrual cycle (41), suggesting that high levels of estradiol in the liver, achievable through the first-pass effect of oral estradiol, may be needed to influence serum SHBG concentrations. Luteal phase plasma progesterone had a univariate correlation with serum SHBG but not by multivariate regression.…”
Section: Discussionmentioning
confidence: 88%
“…SHBG concentrations do not vary during the menstrual cycle, thus a single measurement in the earlier follicular phase is sufficient to define SHBG concentration for the placebo and OCP cycles, and to allow calculations of free androgen index (FAI) for the studied phases of the menstrual cycle. 16 Blood samples were analyzed using (1) the IMMU-LITE analyzer (IMMULITE, Los Angeles, CA) for in vitro quantitative measurement of SHBG in serum; and (2) the ADVIA Centaur System (New York, NY) for in vitro quantitative measurement of total testosterone (bound and unbound) in serum, and the quantitative determination of estradiol, progesterone, follicular-stimulating hormone (FSH), luteinizing hormone (LH) in human serum.…”
Section: Methodsmentioning
confidence: 99%